A Populist Exception? The 2017 New Zealand General Election - Vowles, Jack; Curtin, Jennifer (ANU Press, 2020)
The 'spectre of populism' might be an apt description for what is happening in different parts of the world, but does it apply to New Zealand? Immediately after New Zealand's 2017 general election, populist party New Zealand First gained a pivotal role in a coalition with the Labour Party, leading some international observers to suggest it represented a populist capture of the government. The leader of New Zealand First, Winston Peters, justified his support for Labour as necessary to allow capitalism to 'regain ... its human face'. The new prime minister, Jacinda Ardern, spoke of a kinder, inclusive politics. This book draws on the 2017 New Zealand Election Study to uncover New Zealanders' political attitudes and preferences post-election. Its authors ask: is New Zealand now A Populist Exception? Through detailed empirical analyses of how populism and authoritarianism affected vote choice, opinions about immigration, satisfaction with democracy and the relevance of gender and indigeneity to these issues, this book finds that New Zealand politics today does not reflect the international trend toward ideological polarisation and electoral volatility. The authors argue that inclusive forms of populism can be pluralist if a leader's rhetorical approach recognises 'the people' as diverse and encompassing. A Populist Exception? concludes that although populism has long been a strong current in New Zealand history, contemporary New Zealand exhibits a moderate form of populism, with liberal and pluralist values in balance with a strong commitment to majoritarian democracy.